Aerospace structure adhesive based on carbon fibers and preparation method thereof
By adopting nitric acid oxidation treatment and optimizing stirring process in aerospace adhesives, the dispersion of carbon fiber is improved, and the problem of insufficient performance of traditional adhesives in the aerospace field is solved, high strength and durability are achieved, and the bonding performance is adapted to complex environments is achieved. .
Patent Information
- Application Number
- CN202411244050.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-14
AI Technical Summary
Traditional adhesives are difficult to meet the requirements of high strength, temperature and pressure resistance in the aerospace field, and the uneven dispersion of carbon fibers in adhesives affects the overall performance.
The mass ratio of epoxy resin, curing agent and coupling agent is 10:3:1. The carbon fiber is oxidized by nitric acid, and the polysodium carboxylate dispersant is added by low speed and high speed stirring and batch addition, which is optimized. Preparation process to improve the dispersion of carbon fibers.
It significantly improves the dispersion and bonding properties of the adhesive, improves the bonding strength by 30%, maintains good conditions in the environment of -50℃ to 150℃ and 0 to 5MPa, has good toughness and aging resistance, and extends the structure of the aerospace vehicle Service life.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives for aerospace, and in particular relates to an aerospace structural adhesive based on carbon fiber and a preparation method thereof. Background Art
[0002] With the continuous development of aerospace technology, the performance requirements for materials are increasing. In the structure of aerospace vehicles, adhesives play a vital role. They need to have high strength, good temperature resistance, pressure resistance and reliable bonding performance. Traditional adhesives may not be able to meet the increasingly stringent requirements of the aerospace field in some aspects of performance. Carbon fiber, as a high-performance material, has the advantages of high strength and high modulus. Applying carbon fiber to aerospace structural adhesives is expected to improve the performance of adhesives. However, the dispersion of carbon fiber in adhesives is a key issue. If the dispersion is uneven, it will affect the overall performance of the adhesive.
[0003] In order to solve the dispersion problem of carbon fiber in adhesives and improve the comprehensive performance of adhesives to meet the special needs of the aerospace field, it is necessary to develop an aerospace structural adhesive based on carbon fiber. This adhesive needs to be optimized and innovated in preparation process, component composition, etc. to ensure that the carbon fiber can be well dispersed and the adhesive can maintain excellent bonding properties under different temperature and pressure environments, thereby improving the reliability and safety of aerospace structures. Summary of the invention
[0004] The object of the present invention is to provide an aerospace structural adhesive based on carbon fiber and a preparation method thereof, aiming to solve the problems in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A carbon fiber-based aerospace structural adhesive, characterized in that:
[0007] It contains epoxy resin, curing agent and coupling agent, and the mass ratio of epoxy resin: curing agent: coupling agent is 10:3:1;
[0008] The mass percentage of carbon fiber in the adhesive is 5% to 15%;
[0009] The carbon fibers were surface treated with nitric acid oxidation to improve their dispersibility in the adhesive;
[0010] During the preparation process, the optimized preparation process was adopted, which included a stirring method of first low speed and then high speed, stirring parameters of first stirring at 100 r / min for 10 min and then stirring at 500 r / min for 20 min, and a batch addition method to improve the dispersion of carbon fiber in the adhesive;
[0011] A sodium polycarboxylate dispersant is added to the adhesive system in an amount of 3% of the total mass of the adhesive to improve the dispersibility of the carbon fibers.
[0012] As a preferred solution of the present invention, the purity of the epoxy resin is not less than 99%;
[0013] The particle size of the curing agent is between 10 μm and 50 μm;
[0014] The surface polar group content of the carbon fiber after surface treatment is between 0.5mmol / g and 1mmol / g to ensure good dispersibility and bonding strength with the adhesive matrix.
[0015] As a preferred solution of the present invention, step 1: adding epoxy resin, curing agent and coupling agent into a reaction container in a mass ratio of epoxy resin: curing agent: coupling agent = 10:3:1, and stirring for 10 minutes at a temperature of 80° C. and a stirring speed of 100 r / min;
[0016] Step 2: After the carbon fiber is oxidized by nitric acid, it is added to the mixture of step 1 by slow and uniform addition, and stirring is continued for 20 minutes at a temperature of 100° C. and a stirring speed of 500 r / min. The stirring process adopts intermittent stirring;
[0017] Step 3: Add sodium polycarboxylate dispersant to the mixture in step 2 in an amount of 3% of the total mass of the adhesive, continue stirring for 15 minutes, and then cool, filter, and perform other treatments on the mixture obtained in step 2 to obtain the carbon fiber-based aerospace structural adhesive.
[0018] As a preferred solution of the present invention, the carbon fiber is added in step 2 by slowly and evenly adding;
[0019] After cooling and filtering in step 3, the adhesive needs to be packaged;
[0020] The dispersion of the carbon fibers in the prepared adhesive is tested, and the dispersion uniformity should be such that the carbon fiber agglomeration size does not exceed 5 μm when observed under a microscope.
[0021] As a preferred solution of the present invention, it is used for bonding wings and fuselages of aerospace vehicles;
[0022] Able to maintain good bonding performance in an environment with a temperature range of -50℃ to 150℃ and a pressure range of 0 to 5MPa;
[0023] Due to the good dispersion of carbon fiber, the bonding strength of adhesives in aerospace structures is increased by 30%, and reliability is enhanced.
[0024] As a preferred solution of the present invention, it needs to be stored in an environment with a temperature of 5°C to 25°C and a relative humidity of 30% to 60%;
[0025] The storage container should have characteristics such as good sealing;
[0026] During storage, the carbon fiber should be prevented from agglomerating again and its dispersion in the adhesive should be maintained.
[0027] As a preferred solution of the present invention, the bonding strength is not less than 20MPa;
[0028] The aging resistance performance meets the requirement that the performance decrease does not exceed 10% under the conditions of 1000 hours of illumination and 500 temperature cycles;
[0029] It has good toughness, and the elongation at break is between 5% and 10%;
[0030] The dispersion uniformity of carbon fiber in the adhesive meets the detection index description that the carbon fiber agglomeration size does not exceed 5μm when observed under a microscope.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] Firstly, the dispersion of carbon fiber in the adhesive was significantly improved by nitric acid oxidation treatment of carbon fiber and optimization measures such as low-speed then high-speed stirring, batch addition and addition of sodium polycarboxylate dispersant. This made the overall performance of the adhesive more uniform and stable, avoiding local performance differences caused by carbon fiber agglomeration. Under a microscope, the carbon fiber agglomeration size did not exceed 5μm. Good dispersion laid the foundation for improving the performance of the adhesive. Secondly, the composition and preparation process optimization of the adhesive gave it excellent bonding properties, with a bonding strength of not less than 20MPa, which was greatly improved compared to traditional adhesives, and it can maintain good performance in an environment with a temperature of -50°C to 150°C and a pressure range of 0 to 5MPa. The excellent bonding performance can meet the use requirements of aerospace vehicles in complex environments. At the same time, due to the good dispersion of carbon fiber, the bonding strength of the adhesive in the aerospace structure is increased by 30%, and the reliability is enhanced, which is of great significance for improving the safety of aerospace structures. Furthermore, the adhesive also has good aging resistance, with the performance degradation not exceeding 10% under 1000 hours of illumination and 500 temperature cycles, as well as good toughness, with an elongation at break between 5% and 10%. These performance advantages make its application in the aerospace field more extensive and reliable, and can effectively extend the service life of aerospace vehicle structures and reduce maintenance costs. In short, this new adhesive provides strong support for the development of aerospace technology. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] The present invention provides the following technical solutions:
[0036] A carbon fiber-based aerospace structural adhesive, characterized in that:
[0037] It contains epoxy resin, curing agent and coupling agent, and the mass ratio of epoxy resin: curing agent: coupling agent is 10:3:1;
[0038] The mass percentage of carbon fiber in the adhesive is 5% to 15%;
[0039] The carbon fibers were surface treated with nitric acid oxidation to improve their dispersibility in the adhesive;
[0040] During the preparation process, the optimized preparation process was adopted, which included a stirring method of first low speed and then high speed, stirring parameters of first stirring at 100 r / min for 10 min and then stirring at 500 r / min for 20 min, and a batch addition method to improve the dispersion of carbon fiber in the adhesive;
[0041] A sodium polycarboxylate dispersant is added to the adhesive system in an amount of 3% of the total mass of the adhesive to improve the dispersibility of the carbon fibers.
[0042] In a specific embodiment of the present invention, the mass ratio can ensure a good chemical reaction between the components of the adhesive to form a stable structure. The proportion of carbon fiber is between 5% and 15%, which can not only give full play to the reinforcing effect of carbon fiber, improve the strength and other properties of the adhesive, but also ensure the overall uniformity of the adhesive. Measures such as surface treatment, stirring method and addition of dispersant greatly improve the dispersibility of carbon fiber in the adhesive, make the adhesive performance more uniform and stable, avoid local performance differences, and lay the foundation for subsequent excellent performance.
[0043] Specifically, the purity of the epoxy resin is not less than 99%;
[0044] The particle size of the curing agent is between 10 μm and 50 μm;
[0045] The surface polar group content of the carbon fiber after surface treatment is between 0.5mmol / g and 1mmol / g to ensure good dispersibility and bonding strength with the adhesive matrix.
[0046] In this embodiment: the purity of epoxy resin is not less than 99%, which can ensure its optimal performance in the adhesive and reduce the adverse effects of impurities on the overall quality and performance of the adhesive. The particle size of the curing agent is between 10μm and 50μm, which is conducive to its uniform dispersion in the adhesive and full reaction with other components. The content of polar groups on the surface of carbon fiber is between 0.5mmol / g and 1mmol / g, which can ensure its good dispersibility, so that the carbon fiber can be evenly distributed in the adhesive, while enhancing the bonding force with the adhesive matrix, improving the overall strength and stability of the adhesive, so as to better meet the requirements of aerospace structures for high performance of adhesives and ensure the reliability of aircraft structures.
[0047] Specifically, step 1: adding epoxy resin, curing agent and coupling agent into a reaction container in a mass ratio of epoxy resin: curing agent: coupling agent = 10:3:1, and stirring for 10 minutes at a temperature of 80° C. and a stirring speed of 100 r / min;
[0048] Step 2: After the carbon fiber is oxidized by nitric acid, it is added to the mixture of step 1 by slow and uniform addition, and stirring is continued for 20 minutes at a temperature of 100° C. and a stirring speed of 500 r / min. The stirring process adopts intermittent stirring;
[0049] Step 3: Add sodium polycarboxylate dispersant to the mixture in step 2 in an amount of 3% of the total mass of the adhesive, continue stirring for 15 minutes, and then cool, filter, and perform other treatments on the mixture obtained in step 2 to obtain the carbon fiber-based aerospace structural adhesive.
[0050] In this embodiment: The temperature and stirring conditions of step one can promote the epoxy resin, curing agent and coupling agent to fully mix and react, and make basic preparations for the subsequent addition of carbon fiber and other ingredients. The nitric acid oxidation treatment of carbon fiber in step two further improves its dispersibility. The slow and uniform addition method and specific stirring conditions can better integrate the carbon fiber into the adhesive system, and intermittent stirring helps the reaction to be more complete and uniform. Step three adds a dispersant and continues to stir, which can further improve the dispersibility of the carbon fiber. Subsequent cooling, filtration and other treatments can remove impurities and inadequately reacted substances, and obtain an adhesive with better performance to meet the use requirements of aerospace structures.
[0051] Specifically, in step 2, the carbon fiber is added slowly and evenly.
[0052] After cooling and filtering in step 3, the adhesive needs to be packaged;
[0053] The dispersion of the carbon fibers in the prepared adhesive is tested, and the dispersion uniformity should be such that the carbon fiber agglomeration size does not exceed 5 μm when observed under a microscope.
[0054] In this embodiment: the method of slowly and evenly adding carbon fiber in step 2 can ensure that the carbon fiber is evenly dispersed in the adhesive system, avoiding local agglomeration that affects the performance of the adhesive. Cooling and filtering treatments can make the morphology of the adhesive more stable, remove impurities and other undesirable components, and improve the purity and quality of the adhesive. The packaging treatment can effectively protect the adhesive and prevent it from being contaminated and affected by the external environment during storage and transportation. The detection requirements for the dispersion of carbon fiber ensure the uniformity of the dispersion of carbon fiber in the adhesive, so that the agglomeration size of carbon fiber observed under a microscope does not exceed 5μm, ensuring the uniformity and stability of the adhesive performance and improving its reliability in aerospace structures.
[0055] Specifically, it is used to bond wings and fuselages of aerospace vehicles;
[0056] Able to maintain good bonding performance in an environment with a temperature range of -50℃ to 150℃ and a pressure range of 0 to 5MPa;
[0057] Due to the good dispersion of carbon fiber, the bonding strength of adhesives in aerospace structures is increased by 30%, and reliability is enhanced.
[0058] In this embodiment: the adhesive is used to bond the wings and fuselage of aerospace vehicles, which broadens its application range. The ability to maintain good bonding performance in an environment with a temperature of -50°C to 150°C and a pressure range of 0 to 5MPa means that it can adapt to the requirements of aerospace vehicles in different flight states and environments, whether it is low temperature and low pressure at high altitude or high temperature and high pressure under certain special working conditions. Due to the good dispersibility of carbon fiber, the bonding strength of the adhesive in the aerospace structure is increased by 30%, which greatly enhances the connection strength and stability of the aircraft structure, enhances reliability, effectively reduces the risk of failure of the aircraft structure during flight, and ensures flight safety.
[0059] Specifically, it needs to be stored in an environment with a temperature of 5°C to 25°C and a relative humidity of 30% to 60%;
[0060] The storage container should have characteristics such as good sealing;
[0061] During storage, the carbon fiber should be prevented from agglomerating again and its dispersion in the adhesive should be maintained.
[0062] In this embodiment: the adhesive is stored in an environment with a temperature of 5°C to 25°C and a relative humidity of 30% to 60%, which can effectively prevent the adhesive from deteriorating or performance degradation due to excessively high or low temperature, excessively high or low humidity. The storage container has the characteristics of good sealing, which can prevent the adhesive from contacting with external air, moisture, etc., prevent it from being contaminated and oxidized, and maintain the stability of the performance of the adhesive. During the storage process, the carbon fiber is prevented from agglomerating again and its dispersion state in the adhesive is maintained, which can ensure that the adhesive still has good performance when used, extend the service life of the adhesive, and reduce performance loss and waste caused by improper storage.
[0063] Specifically, the bonding strength is not less than 20MPa;
[0064] The aging resistance performance meets the requirement that the performance decrease does not exceed 10% under the conditions of 1000 hours of illumination and 500 temperature cycles;
[0065] It has good toughness, and the elongation at break is between 5% and 10%;
[0066] The dispersion uniformity of carbon fiber in the adhesive meets the detection index description that the carbon fiber agglomeration size does not exceed 5μm when observed under a microscope.
[0067] In this embodiment: the bonding strength is not less than 20MPa, which ensures that the adhesive has sufficient connection strength in the aerospace structure and can firmly bond the various components of the aircraft. The aging resistance meets the requirement that the performance decreases by no more than 10% under the illumination time of 1000h and the temperature cycle number of 500 times, indicating that the adhesive has good stability and durability, can maintain good performance during long-term use, and adapt to the use requirements of aerospace aircraft in different environments and time. Good toughness, elongation at break between 5% and 10%, so that the adhesive has a certain buffering and adaptability when subjected to external forces, improves the impact resistance and reliability of the aircraft structure, and can also better adapt to the vibration of the aircraft during flight, etc., to ensure the integrity and safety of the aircraft structure. The uniformity of the dispersion of carbon fiber in the adhesive meets the detection index, further ensuring the uniformity and stability of the adhesive performance.
[0068] The working principle and use process of the present invention:
[0069] First, in the preparation process, epoxy resin, curing agent and coupling agent are added to the reaction container according to the mass ratio of epoxy resin: curing agent: coupling agent = 10:3:1, and stirred at 80°C and 100r / min for 10 minutes. Then, the carbon fiber is oxidized with nitric acid to improve its dispersibility in the adhesive, and then the treated carbon fiber is added to the above mixture in a slow and uniform manner. At this time, the temperature rises to 100°C, the stirring speed is changed to 500r / min, and the intermittent stirring is carried out for 20 minutes. After that, a sodium polycarboxylate dispersant accounting for 3% of the total mass of the adhesive is added to the mixture, and stirring is continued for 15 minutes. Subsequently, the obtained mixture is cooled, filtered, and packaged. In terms of application, the adhesive is used to bond the wings and In the fuselage and other parts, it can maintain good bonding properties in the temperature range of -50℃ to 150℃ and the pressure range of 0 to 5MPa. Due to the adoption of a variety of measures to improve the dispersion of carbon fiber, the bonding strength of the adhesive in aerospace structures has increased by 30%, and the reliability has been enhanced. When storing, it needs to be placed in a storage container with a temperature of 5℃ to 25℃, a relative humidity of 30% to 60% and good sealing. At the same time, it is necessary to avoid the re-agglomeration of carbon fiber to maintain its dispersion in the adhesive, and its performance indicators are shown as a bonding strength of not less than 20MPa, a performance degradation of no more than 10% under a light exposure time of 1000h and a temperature cycle of 500 times, an elongation at break of between 5% and 10%, and the uniformity of the dispersion of carbon fiber in the adhesive meets the standard that the carbon fiber agglomeration size does not exceed 5μm when observed under a microscope.
[0070] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A carbon fiber-based aerospace structural adhesive, characterized in that: It contains epoxy resin, curing agent and coupling agent, and the mass ratio of epoxy resin: curing agent: coupling agent is 10:3:1; The mass percentage of carbon fiber in the adhesive is 5% to 15%; The carbon fibers were surface treated with nitric acid oxidation to improve their dispersibility in the adhesive; During the preparation process, the optimized preparation process was adopted, which included a stirring method of first low speed and then high speed, stirring parameters of first stirring at 100 r / min for 10 min and then stirring at 500 r / min for 20 min, and a batch addition method to improve the dispersion of carbon fiber in the adhesive; A sodium polycarboxylate dispersant is added to the adhesive system in an amount of 3% of the total mass of the adhesive to improve the dispersibility of the carbon fibers.
2. The carbon fiber-based aerospace structural adhesive according to claim 1, characterized in that: The purity of the epoxy resin is not less than 99%; The particle size of the curing agent is between 10 μm and 50 μm; The surface polar group content of the carbon fiber after surface treatment is between 0.5mmol / g and 1mmol / g to ensure good dispersibility and bonding strength with the adhesive matrix.
3. The method for preparing a carbon fiber-based aerospace structural adhesive according to claim 2, characterized in that: The following steps are involved: Step 1: Add epoxy resin, curing agent and coupling agent into a reaction vessel in a mass ratio of epoxy resin: curing agent: coupling agent = 10:3:1, and stir for 10 minutes at a temperature of 80°C and a stirring speed of 100 r / min; Step 2: After the carbon fiber is oxidized by nitric acid, it is added to the mixture of step 1 by slow and uniform addition, and stirring is continued for 20 minutes at a temperature of 100° C. and a stirring speed of 500 r / min. The stirring process adopts intermittent stirring; Step 3: Add sodium polycarboxylate dispersant to the mixture in step 2 in an amount of 3% of the total mass of the adhesive, continue stirring for 15 minutes, and then cool, filter, and perform other treatments on the mixture obtained in step 2 to obtain the carbon fiber-based aerospace structural adhesive.
4. The method for preparing a carbon fiber-based aerospace structural adhesive according to claim 3, characterized in that: In step 2, the carbon fiber is added slowly and evenly. After cooling and filtering in step 3, the adhesive needs to be packaged; The dispersion of the carbon fibers in the prepared adhesive is tested, and the dispersion uniformity should be such that the carbon fiber agglomeration size does not exceed 5 μm when observed under a microscope.
5. The use of a carbon fiber-based aerospace structural adhesive according to claim 4, characterized in that: Used for bonding wings and fuselages of aerospace vehicles, etc.; Able to maintain good bonding performance in an environment with a temperature range of -50℃ to 150℃ and a pressure range of 0 to 5MPa; Due to the good dispersion of carbon fiber, the bonding strength of adhesives in aerospace structures is increased by 30%, and reliability is enhanced.
6. A method for storing a carbon fiber-based aerospace structural adhesive according to claim 5, characterized in that: It needs to be stored in an environment with a temperature of 5°C to 25°C and a relative humidity of 30% to 60%; The storage container should have characteristics such as good sealing; During storage, the carbon fiber should be prevented from agglomerating again and its dispersion in the adhesive should be maintained.
7. The performance index of the carbon fiber-based aerospace structural adhesive according to claim 6 is characterized by: The bonding strength is not less than 20MPa; The aging resistance performance meets the requirement that the performance decrease does not exceed 10% under the conditions of 1000 hours of illumination and 500 temperature cycles; It has good toughness, and the elongation at break is between 5% and 10%; The dispersion uniformity of carbon fiber in the adhesive meets the detection index description that the carbon fiber agglomeration size does not exceed 5μm when observed under a microscope.